International Handbook of Career Guidance - Athanasou, James A.; Esbroeck, Raoul Van.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2008)
The International Handbook of Career Guidance represents a project of inter- tional professional cooperation. It is intended as a catalyst for reform and was designed to support the development of career guidance in the years to come. Working for over four years from Belgium and Australia we had the privilege to collaborate with over 50 colleagues throughout the world to produce this Handbook. In every instance we selected key researchers who have an established reputation in the field of career development. They agreed to be involved and we are grateful for their support in this major effort. In this handbook we have tried to bring together a collection that summarises the diverse aspects of career guidance. It is a synthesis of the domain of career and vo- tional guidance firstly for an international readership and secondly it is designed to act as a reference for academics, researchers and professionals in the expanding field of career development. For this reason the Handbook includes coverage of the ba- ground and history of guidance right through to poignant issues relating to careers in the modern world of work. Policy issues relating to the provision of careers services as well as professional issues relating to career education, career counselling, career assessment, program evaluation and research methodologies are covered.
Educational and Vocational Guidance in a Social Context -- Introduction: An International Handbook of Career Guidance -- Career Guidance in a Global World -- Social Contexts for Career Guidance Throughout the World -- Landscape with Travellers: The Context of Careers in Developed Nations -- Theoretical Foundations -- Helping People Choose Jobs: A History of the Guidance Profession -- The Big Five Career Theories -- Recent Developments in Career Theories: The Influences of Constructivism and Convergence -- Decision-Making Models and Career Guidance -- A Constructivist Approach to Ethically Grounded Vocational Development Interventions for Young People -- Social Contexts for Career Guidance Throughout the World. Developmental-Contextual Perspectives on Career Across the Lifespan -- Theories in Cross-Cultural Contexts -- Educational and Vocational Guidance in Practice -- Career Guidance and Counselling in Primary and Secondary Educational Settings -- On the Shop Floor: Guidance in the Workplace -- Career Management: Taking Control of the Quality of Work Experiences -- Qualification Standards for Career Practitioners -- The Emergence of More Dynamic Counselling Methods -- Career Guidance and Public Policy -- Training Career Practitioners in the 21st Century -- Educational and Vocational Guidance with Specific Target Groups -- Guidance for Girls and Women -- Career Guidance for Persons with Disabilities -- Career Guidance with Immigrants -- Coping with Work and Family Role Conflict: Career Counselling Considerations for Women -- Career Guidance for at Risk Young People: Constructing a Way Forward -- Testing and Assessment in Educational and Vocational Guidance -- Testing and Assessment in an International Context: Cross-and Multi-Cultural Issues -- Career Maturity Assessment in an International Context -- Interest Assessment in an International Context -- Assessment of Values and Role Salience -- Cognitive Measurement in Career Guidance -- Qualitative Career Assessment: A Higher Profile in the 21st Century? -- Ethical Issues in Testing and Assessment -- Evaluation of Educational and Vocational Guidance -- Quantitative Research Synthesis: The Use of Meta-Analysis in Career Guidance and Vocational Psychology -- Action Theory: An Integrative Paradigm for Research and Evaluation in Career -- Using Longitudinal Methodology in Career Guidance Research -- Evaluation of Career Guidance Programs -- Conclusion -- An International and Social Perspective on Career Guidance.
Keywords: Education; Educational policy; ducation and state; Educational sociology; Assessment; Education and sociology; Sociology, Educational; Education; Professional & Vocational Education; Assessment, Testing and Evaluation; Educational Policy and Politics; Sociology of Education; Electronic books